2004
DOI: 10.4319/lo.2004.49.4_part_2.1408
|View full text |Cite
|
Sign up to set email alerts
|

Testing zooplankton food limitation across gradients of depth and productivity in small stratified lakes

Abstract: We examined the significance of vertical structure in lake plankton to grazer-resource coupling by quantifying how the intensity and mechanism of grazer food limitation varies with depth. We used Daphnia growth assays and also sampled resources (chlorophyll, particulate carbon, and phosphorus) and the day/night depth distributions of Daphnia spp. during summer in four depth strata of lakes that differ in trophic state. The growth assays included treatments with natural seston and seston supplemented with phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Food resources are well known to exert profound effects on zooplankton abundance and composition through one or more major avenues of influence (e.g. Sterner and Schulz, 1998;DeMott et al, 2004;Becker, 2004):…”
Section: Inter-annual Variation In Zooplankton Community Compositionmentioning
confidence: 99%
“…Food resources are well known to exert profound effects on zooplankton abundance and composition through one or more major avenues of influence (e.g. Sterner and Schulz, 1998;DeMott et al, 2004;Becker, 2004):…”
Section: Inter-annual Variation In Zooplankton Community Compositionmentioning
confidence: 99%
“…Two important consequences of this are that more transparent lakes have lower food quality (higher carbon : phosphorus [C : P]) in the surface waters (Sterner et al 1997) and that the food in the DCM is likely to be of higher nutritional quality than that in the surface waters (Rothhaupt 1991). A comparison of food quality across lakes of differing transparency showed that both oligotrophic and eutrophic lakes have lower seston C : P ratios (higher food quality) in deeper waters, and that the pattern is stronger in more oligotrophic lakes (DeMott et al 2004). This same study also showed higher particulate carbon concentrations in the deeper waters of both types of lakes, higher edible chlorophyll in the deeper waters of the eutrophic lake, and similar edible chlorophyll across all depths in the oligotrophic lake.…”
mentioning
confidence: 99%
“…Studies that have fed zooplankton with seston collected from epilimnetic and deeper waters in controlled experiments frequently reveal equal or higher growth and reproductive rates on the food from deeper waters (Williamson et al 1996a;Winder et al 2003a;DeMott et al 2004). In some cases, the depth of optimal food quality may vary seasonally (Hoenicke and Goldman 1987), and in others, food quality may actually be better in the surface waters (Cole et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The S f values in the three cladoceran species were estimated for two food concentrations (i.e., 10 4 and 5 3 10 4 cell mL 21 ), both of which are environmentally realistic (DeMott et al 2004). The AE values at the 5 3 10 4 cells mL 21 food level (24.5%, 32.0%, and 57.4% in C. dubia, D. galeata, and M. macrocopa, respectively) were estimated by fitting an exponential decay model with food concentration to the quantified Cd AE (Tan and Wang 2009).…”
Section: Discussionmentioning
confidence: 99%